The Rhetorical Structure of Abstracts Written by International Authors in Reputable International Journals in Applied Linguistics - Marpaung, Tiara Azzahra; Sasmita, Ruwaiza; Dewi, Anggun Citra Sari (Edu-Ling: Journal of English Education and Linguistics, 2024)
In research articles, abstract was defined as a mini-article because it consists of summary of the study. Abstract was a very important part because abstract used to encouraged the readers to saw the other sections of the article. It was because in general the abstract was the first part that readers would read. This present study conducted to investigate the rhetorical structure used in abstract of research articles in applied linguistics written by international authors and published in reputable international journals. This study used content analysis method with the abstract framework that purposed by Swales and Feak (2009). The data were collected from 20 research articles from reputable international journals in applied linguistics. The findings showed that from five moves, there were two moves which were Move 3 (Methods) and Move 4 (Results/findings) are categorized as obligatory. Meanwhile for other moves, which are Move 1 (Introduction), Move 2 (Purpose/aim), and Move 5 (Conclusion/suggestion) are categorized as conventional. This reasearch  provided the knowledge about the rhetorical structured of the abstract in research articles written by international authors and published in reputable international journals to increase the national author’s awareness of the importanced of the five moves that purposed by Swales and Feak (2009) in conducting the abstract.